IMPLEMENTATION OF PROFIT SHARING AGREEMENT FOR INLAND FISHERY PRODUCT BETWEEN PONDS OWNERS AND CULTIVATORS - Irmawati Ambo; Andi Purnawati (Omnibus Law Journal, 2021)
South Banawa District is one of the sub-districts in the Donggala Regency which has aquaculture land, although only a small part of the land is technically managed but has produced thousands of tons of shrimp and milkfish every year, this can happen because South Banawa District is a an area that has an area consisting of mountains, rice fields, aquaculture and the sea. The occurrence of an agreement for land fishery products sharing, in Banawa District, because on the one hand the pond owners do not have time to manage their ponds, there are even pond owners who do not have expertise in the field of ponds and on the other hand there are cultivators who do not have ponds, but they have expertise in that field. This is indeed quite reasonable, because it has become an undeniable reality that not all cultivators have land to manage in order to meet the needs of living with their families. In fact, many of the farmers had no land or ponds to cultivate at all. Considering that the fisheries business is complex, the overall regulatory effort will have a positive impact on the development of the fishery business itself.